An in Vitro Analysis of Antibacterial Efficacy of Local Brands of Toothpastes and Mouthrinses in Malaysian Market on Selected Oral Pathogens - Chandramohan, M; W Chan, S; Paulraj, P; T Mohamed Javad, P; Sajeesh, P; P Sajna, K; Ketharin, T (International Journal of Engineering and Technology, 2019)
Oral disease affects a considerable portion of population and is considered one of the major causes of tooth loss in developed and developing countries. An in vitro study was conducted to investigate the antimicrobial efficacy of toothpastes and mouthrinses towards oral pathogens which are found to cause most of the oral diseases such as gingivitis and dental plague. In this study, a total of five toothpastes and four mouthrinses were investigated for their antimicrobial activity against five oral pathogens such as Streptococcus salivarius, Streptococcus sanguis, Streprococcus oralis, Streptococcus mutans and Candida albicans. The efficacy of different concentration of the toothpastes and mouthrinses were assessed by agar well diffusion method. Statistical analysis was performed by using analysis of variance (ANOVA) with post-hoc least square differences (LSD) method (p=0.05). Toothpaste B gave the maximum zone of inhibition against tested organisms, Streptococcus sanguis and Streptococcus oralis. Toothpaste C and E gave the maximum zone of inhibition against Streptococcus salivarius and Streptococcus mutans respectively. Toothpaste A was most effective against Candida albicans. Mouthrinse G was most effective against Streptococcus salivarius, Streptococcus sanguis, Streptococcus oralis and Candida albicans. In conclusion, the present study has demonstrated that dentifrices which contain fluoride and cetylpyridium chloride formulation gave the maximum zone of inhibition against the tested organisms compared to other activeÂ ingredients.